Facile synthesis and characterization of metal ions (Ce, Cu, Gd, Mn and Y) doped Nickel Oxide nanostructures for spintronic and photodiode applications. (1st September 2022) - Marnadu, R; Venkatesan, S; Alkallas, Fatemah H; Ben Gouider Trabelsi, Amira; Shkir, Mohd; AlFaify, S
Abstract: Multiphase hexagon and flower-shaped structures of NiO nanocomposites have been prepared with different metal ions (Ce, Cu, Gd, Mn and Y) using facile and low-cost co-precipitation method. The optical, structural, morphological, and magnetic properties of the synthesized nanostructures have been investigated. The XDR measurement reveals the coexistence of several crystal structures like cubic, monoclinic, tetragonal, and orthorhombic which unveils the formation of polymorphism in the nanocomposites with high crystallinity. A wideband has been located in the FT-IR spectra at around 600 cm −1 revealing the metal oxide (M-O) phase formation. DRS exhibits four large and intense absorption bands at 260, 380, 420, and 720 nm in the UV and visible domains assigned to the nanocrystalline phases of NiO, CuO, CeO, and MnO, respectively. SEM images of metal-doped nickel oxide nanocomposites show a white sponge, semi-spherical, flower-like, and hexagon-shaped particles of 15 nm size. TEM result establishes a smooth surface for samples grown from gadolinium and yttrium, contrary to other samples made off cerium and manganese demonstrate a rough surface. A ferromagnetic tendency has been located for samples prepared from copper, manganese, and gadolinium-based NiO nanocomposites with coercivities of 132, 113, and 26 Oe, correspondingly. Photodiode characteristics were also investigated on the developed devices. These outcomes signify their use in spintronic and optoelectronic industries.